Zambia Engaging the Private Sector in Education : SABER Country Report 2016 - Baum, Donald Rey; De Brular, Laura Lewis (World Bank, Washington, DC, 2017)
This report presents an analysis of how effectively the current policies of Zambia engage the private sector in basic (primary and secondary) education. The analysis draws on the engaging the private sector (EPS) framework, a product of the World Bank’s systems approach for better education results (SABER). SABER-EPS research in Zambia has found that despite impressive gains in enrollment, education quality remains a serious concern, as does equity - especially beyond the primary level. School providers in Zambia include private schools, community schools, and grant-aided schools. Non-government schools account for a sizable share of education service provision in the country. Based on a review of existing policies, SABER-EPS offers the following recommendations for Zambia to enhance its engagement with the non-state sector in education and to meet the challenges of access, quality, and equity: strengthen system accountability measures; consider a needs-based inspection system where underperforming schools receive greater scrutiny and support; and increase the information available to parents on school quality, including via school report cards. The report provides an overview of SABER-EPS, followed by a description of the basic education system in Zambia, with a focus on the non-state sector and government policies related to the private provision of education. The report then benchmarks Zambia’s policy environment utilizing the SABER-EPS framework and finally offers policy options to enhance learning for all children in primary and secondary school.